GLP-1 and GIP receptor agonists in the treatment of Parkinson’s disease: Translational systematic review and meta-analysis protocol of clinical and preclinical studies - Vaccari, Carolina [UNESP]; Grotto, Denise; Pereira, Tiago da V.; de Camargo, João Lauro V. [UNESP]; Lopes, Luciane C. (Public Library of Science (PLoS), 2021)
Background Parkinson’s disease (PD) is a progressive multifactorial neurodegenerative condition. Epidemiological studies have shown that patients with type 2 diabetes mellitus (T2DM2) are at increased risk for developing PD, indicating a possible insulin-modulating role in this latter condition. We hypothesized that drugs similar to glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP), used in the treatment of T2DM2, may play a role in PD. Objectives The purpose of this study is to systematically review and meta-analyze data of preclinical and clinical studies evaluating the efficacy and safety of GLP-1 and GIP drugs in the treatment of PD. Methods Two reviewers will independently evaluate the studies available in the Ovid Medline, Ovid Embase, Web of Science, Cochrane Central Register of Controlled Trials, Cinahl, and Lilacs databases. Preclinical rodent or non-human primate studies and randomized controlled human clinical trials will be included, without language or publication period restrictions. Outcomes of interest in preclinical studies will be primarily locomotor improvements and adverse effects in animal models of PD. For clinical trials, we will evaluate clinical improvements rated by the Movement Disorders Society Unified Parkinson’s Disease Rating Scale–parts I, II, III, and IV, and adverse effects. The risk of bias of preclinical studies will be assessed by the SYRCLE tool and CAMARADES checklist and the clinical studies by the Cochrane tool; the certainty of the evidence will be rated by GRADE. Discussion and conclusion There is an urge for new PD treatments that may slow the progression of the disease rather than just restoring dopamine levels. This study will comprehensively review and update the state of the art of what is known about incretin hormones and PD and highlight the strengths and limitations of translating preclinical data to the clinic whenever possible. Systematic review registration PROSPERO registration number CRD42020223435.